Hubungan antara tingkat pendidikan dengan kualitas pekerjaan karyawan di perusahaan pengolahan ikan pada PT. Triko Bina Nusantara Di Desa Dongkala Kecamatan Pasarwajo Kabupaten Buton - Lita, Wa; Mansyur, Akhmad; Budiyanto; Patadjai, Andi Besse; Patiung, Seventry Meliana (Jurnal Sosial Ekonomi Perikanan, 2023)
This study aims to determine the relationship between the level of education with the quality of work of employees at PT. Triko Bina Nusantara. this research was conducted in Dongkala village, Pasarwajo district, Buton regency during September to October 2020. the method used in this study is the census method, with a total of 30 respondents. the analysis used is chi-square. the data consists of the level of education and quality of work of employees. the results showed that the relationship between the level of education and the quality of work has a significance value of 0,319>(0,05), which means that there is no relationship between the level of education with the quality of work of employees at PT. Triko Bina Nusanatara.